2019
DOI: 10.1002/chir.23103
|View full text |Cite
|
Sign up to set email alerts
|

Use of chiral auxiliaries in the asymmetric synthesis of biologically active compounds: A review

Abstract: This review article describes the use of some of the most popular chiral auxiliaries in the asymmetric synthesis of biologically active compounds. Chiral auxiliaries derived from naturally occurring compounds, such as amino acids, carbohydrates, and terpenes, are considered essential tools for the construction of highly complex molecules. We highlight the auxiliaries of Evans, Corey, Yamada, Enders, Oppolzer, and Kunz, which led to remarkable progress in asymmetric synthesis in the last decades and continue to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 176 publications
(231 reference statements)
0
36
0
Order By: Relevance
“…chiral auxiliary induced chirality strategy because the carboxylate can be served as a handle for the incorporation of a chiral auxiliary 63 . However, they are rarely employed in radical processes 64,65 probably because of the high reactivity of radial species.…”
Section: Resultsmentioning
confidence: 99%
“…chiral auxiliary induced chirality strategy because the carboxylate can be served as a handle for the incorporation of a chiral auxiliary 63 . However, they are rarely employed in radical processes 64,65 probably because of the high reactivity of radial species.…”
Section: Resultsmentioning
confidence: 99%
“…A final and more novel approach can be seen in a 2005 paper published by Mendoza that discloses access to N ‐substituted TZD structures derived from oxazolidinethiones [23] . Chiral auxiliaries have been used to construct bioactive compounds [24] . The chiral auxiliary used in Mendoza‘s work can be seen as a derivative of the renowned Evans auxiliary ( 18 ), with the only difference being a replacement of the carbonyl function to a thione ( 19 ).…”
Section: Substitution Reactionsmentioning
confidence: 99%
“…Zakarian et al reported direct methylation of ( S )-naproxen using a chiral enolate, as shown in Scheme 17 . In contrast to conventional chiral alkylation requiring chiral auxiliary attachment and detachment [ 62 , 63 ], this chiral enolate (reagent) gives the desired product directly in a highly stereoselective manner. Although the author reported that the recovery of chiral amines was possible and readily available [ 64 ], excess use of base and electrophile needs to be improved for further application and industrial-scale synthesis.…”
Section: Recent Synthetic Advances In Naproxenmentioning
confidence: 99%